Logged In: YES
user_id=501686
Observed in 5.9.3cvs.
factor((2*t+2)^(2/3) ) => 2^(2/3)*(t+1)^(2/3) OK
factor((-2*t-2)^(2/3) ) => 2^(2/3)*(t+1)^(2/3) OK
(note that (-1)^(2/3)=1)
But
factor((-t-1)^(2/3)) => (-t-1)^(2/3) ???
should be (t+1)^(2/3)
and these don't work, either:
scanmap(factor,(-t-1)^(2/3))
scanmap(factor,(-t-1)^(2/3),bottomup)
substpart(factor(piece),(-t-1)^(2/3),1)
though peculiarly (and correctly), this does:
factor(-t-1)^(2/3) => (t+1)^(2/3)
Logged In: YES
user_id=501686
Observed in 5.9.3cvs.
Log in to post a comment.